New strategy to mitigate urban heat island effect: Energy saving by combining high albedo and low thermal diffusivity in glass ceramic materials. (June 2017) - Enríquez, E.; Fuertes, V.; Cabrera, M.J.; Seores, J.; Muñoz, D.; Fernández, J.F.
Highlights: Development of new glass ceramic was successfully prepared by 1 step ceramic process. Provides high albedo and low thermal diffusivity: great candidates for cool roofs. Exceptional solution for reducing the urban heating and provide energy saving. Provides higher resistance and durability than conventional reflective methods. Abstract: The Global warming is a real problem that attracts great amount of investigations in order to reduce its adverse impact over the planet. The reduction of the heat island effect and the energy consumption into the building areas is an urgent goal. An interesting solution consists in the use of cool roofs, based on high reflective and high emissivity coatings. However, today, some cool roof materials possess some major drawbacks as high solar degradation, decrease of NIR reflection in comparison with the visible reflection and aesthetic restrictions. In order to overcome such limitations, in this work, a tile coated with a new glass ceramic material has been developed in order to improve the solar reflective properties and to reduce its thermal conductivity and increase the specific heat. These three parameters are key to obtain low thermal diffusivity materials to serve as efficient cool roof applications. The increase in solar reflectivity is complimented also by a high reflectivity in the NIR range that results highly convenient for colored materials. These combined properties in addition of increasing the albedo also contributed to improve the thermal comfort sensation inside the buildings. Therefore a great energy saving over 20% is determined in comparison with conventional ceramic tiles. In addition, these materials also offer a structural solution for durable facades and allow a great decorative variability.